CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

HOXD11 upregulates JAM-A and exerts oncogenic properties via NF-κB signaling pathway in esophageal squamous cell carcinoma - Rong Xiong; Qiongxian Long; Xuqian Zhang; Jun Xu; Yanqun Liu; Li Xiong; Siyun Yang; Gang Feng; Guiqing Song; Kang Liu (Human Cell, 2022)

ERas regulates cell proliferation and epithelial–mesenchymal transition by affecting Erk/Akt signaling pathway in pancreatic cancer - Yang Liu; Peng Qin; Rong Wu; Lianfang Du; Fan Li (Human Cell, 2020)
Pancreatic cancer is the fourth most common lethal malignancy with an overall 5-year survival rate of less than 5%. ERas, a novel Ras family member, was first identified in murine embryonic stem cells and is upregulated in various cancers. However, the expression and potential role of ERas in pancreatic cancer have not been investigated. In this study, we found that ERas mRNA and protein were upregulated in pancreatic cancer tissues and cells compared with controls. Knockdown of ERas in pancreatic cancer cells by siRNA significantly decreased cell proliferation, colony formation, migration, and invasion and promoted cell apoptosis in vitro. Epithelial–mesenchymal transition (EMT) is closely related to tumor progression. We observed a significant decrease in N-cadherin expression in pancreatic cancer cells in response to ERas gene silencing by immunofluorescence assay and western blot. Furthermore, tumor growth and EMT were inhibited in xenografts derived from pancreatic cancer cells with ERas downregulation. We further investigated the regulatory mechanisms of ERas in pancreatic cancer and found that ERas may activate the Erk/Akt signaling pathway. Moreover, Erk inhibitor decreased pancreatic cancer cells proliferation and colony formation activities. Our data suggest that targeting ERas and its relevant signaling pathways might represent a novel therapeutic approach for the treatment of pancreatic cancer.